Peculiar ultrastructural characteristics of fungal cells and of other elements apposed to and in vessel walls in plants of a susceptible carnation cultivar, infected with Fusarium oxysporum f.sp. dianthi race 2 - B. Ouellette, Guillemond; P. Baayen, Robert; Rioux, Danny; Simard, Marie (Phytoprotection, 2004)
AbstractUltrastructural characteristics and cytochemical reactions of unusual, irregular elements (IE) in vessel elements in susceptible carnation plants infected with Fusarium oxysporum are reported. As revealed by labelling for chitin, fungal cells in contact with host cell walls or content had altered or defective lucent layers, and labelling was frequently associated with their outer, opaque layer or matter located outside the cells. Coating matter on vessel walls occurred at all stages of infection, and IEs only in later stages. IEs were delineated by opaque, often folded bands, some contouring pit borders, and contained membranous and vesicular structures mixed with other fine components. Only then, IEs were strongly but not uniformly labelled for chitin. Coating, IE-delineating bands, and the opaque outer layer of typical fungal cells were texturally similar, not labelled for chitin or cellulose, except where they impinged upon host walls. Both probes for chitin and cellulose strongly attached to vessel secondary walls. IEs were often confluent with coating, and with fungal cells connected to them by means of microfilamentous structures. Similar microfilamentous structures and opaque bands connected to IEs, the coating, and the microhyphae, or protruding from fungal cells reached into host walls, associated with alterations of these walls. The possible malleable IEs might be a counterpart of the coating, and although they do not occur in the initial stages of the disease, they could play an important role in the final stages of tissue degradation.